Chemical mediation between Allomerus demerarae Wheeler, 1935 (Hymenoptera: Formicidae) and Cordia nodosa Lam. (Boraginaceae) - ARAUCO-A., ROXANA; IANNACONE-O., JOSE; EDWARDS, DAVID; YU, DOUGLAS (Revista Colombiana de Entomología, 2006)
The chemical interactions between “patrolling” and “domatia” workers of Allomerus demerarae Wheeler, 1935 and the plant myrmecophylic Cordia nodosa Lam were investigated. Differences between the intensity of attraction of ants toward the volatile compounds of four chemical stimuli were determined: extracts of young leaves, of mature leaves, of C. nodosa inflorescences and of A. demerarae eggs-larvae. In 2002, plants and ants were collected at the tourist lodge “Libertador Jungle Lodge” located in the buffer zone of the Tambopata National Reserve, Madre de Dios, Peru. In this symbiosis, chemical mediation has been demonstrated to make the behavior of A. demerarae effective. The results showed that volatile compounds emitted by young leaves are sufficient to prompt the protective patrolling behavior of A. demerarae workers. In contrast, “domatia” worker ants showed a greater attraction to A. demerarae eggs-larvae and C. nodosa flowers. Results suggest the existence of polyethism in A. demerarae colonies in which two worker groups with different functions have been identified. On the basis of these results, two subcastes are suggested, “nursery ants”, which are found inside domatia and are in charge of the behavior of “castration” of C. nodosa flowers, and “patrolling ants”, which were observed on young leaves.